2022
DOI: 10.1097/mcc.0000000000000991
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal hypertension and abdominal compartment syndrome

Abstract: Purpose of reviewIntra-abdominal hypertension (IAH) has been acknowledged as an important contributor to organ dysfunction in critically ill patients, both in surgical and medical conditions. As our understanding of the pathophysiology evolves, risk factors are better recognized, preventive measures can now be implemented and therapeutic interventions tailored to the physiology of the patient. In the current review, we want to highlight developing insights in the epidemiology and treatment of patients with IAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…While many attempts have been made to improve and/or simplify IAP measurement, research has shown that none of these novel techniques is truly superior to the standard, transvesical route. Additionally, biomarkers and imaging have also been tested, which were also not ready to replace traditional IAP measurement for the diagnosis of IAH or ACS [ 6 ]. Current treatment guidelines remain largely unchanged, with nonoperative management options as the preferred strategy for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…While many attempts have been made to improve and/or simplify IAP measurement, research has shown that none of these novel techniques is truly superior to the standard, transvesical route. Additionally, biomarkers and imaging have also been tested, which were also not ready to replace traditional IAP measurement for the diagnosis of IAH or ACS [ 6 ]. Current treatment guidelines remain largely unchanged, with nonoperative management options as the preferred strategy for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies showed that the activated. [27] renin-angiotensin system (RAS) increased significantly, renal resistance increased and glomerular filtration decreased in SAP patients with hypotension and hypovolemia. [28,29]…”
Section: Complications Of Abdominal Compartment Syndromementioning
confidence: 99%